Waste Donation: Empirical Analysis of Faith-Based Ecological Ethics in Indonesia - Fauzia, Ine; Nasrudin, Nasrudin; Suteja Wiradana Kusuma, (Al-Muamalat: Jurnal Ekonomi Syariah, 2025)
This study aims to examine eco-piety, the relationship between religious obedience of the community and environmentally friendly behaviour, one of which is waste donation. Two points follow from this waste donation: firstly, donation (shadaqa) is a simple practice considered light yet with an extraordinary impact for both the giver and the recipient. Secondly, it benefits waste management through recycling, reuse, or repurposing. This practice is muamalah and, at the same time, has environmental impacts. Combining qualitative and quantitative methods, data were collected through literature reviews and interviews, and a survey employing a convenience sampling procedure of West Java residents who completed an e-questionnaire distributed via Google Forms. The data were analysed using logistic regression. The study found that the values of religious obedience and environmentally friendly behaviour are not strongly related. 78% of respondents identified themselves as devout Muslims, and 83% knew verses and hadiths related to environmental protection. From these figures, it is hoped that the figure is directly proportional to the high public interest in giving waste alms, thereby helping to overcome the waste problem in Indonesia, especially in West Java. However, only 54% supported the waste charity program. Further research is needed to demonstrate how this waste charity can be implemented effectively to provide financial, environmental, and religious benefits.